2011
DOI: 10.1108/17579881111173767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interactive thematic maps on tourist perceptions: a network analysis

Abstract: Purpose -The purpose of this paper is to test if and how interactive thematic maps can encourage the formation of tourists' perceptual maps of attractions in a destination. Design/methodology/approach -Data were derived from 365 online trip planners generated by users of the Amish Country web site from 1 August 2007 to 31 July 2008. Given the nature of the data set, network analysis techniques were used to analyze the data. Findings -Network analysis findings demonstrate that the things to do (TTD) included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Moreover, several significant decisions such as restaurants or sites to visit are made in the site because of the role of technology as a facilitator of information. These results support the analysis of Chung et al (2011) who studied the influence of online content such as interactive maps in tourism consumer behaviour. Network analysis demonstrated that interactive maps increase the perceptions of engagement and trip planning in heritage activities more than traditional list displays.…”
Section: Pre-consumption Stagesupporting
confidence: 85%
“…Moreover, several significant decisions such as restaurants or sites to visit are made in the site because of the role of technology as a facilitator of information. These results support the analysis of Chung et al (2011) who studied the influence of online content such as interactive maps in tourism consumer behaviour. Network analysis demonstrated that interactive maps increase the perceptions of engagement and trip planning in heritage activities more than traditional list displays.…”
Section: Pre-consumption Stagesupporting
confidence: 85%
“…Özturan and Roney (2004) examined the Internet use of travel agencies in Turkey, and found that their websites did not have the interactive features required for Internet marketing. Young Chung et al (2011) explored the use of interactive thematic maps on tourist perceptions, using a network analysis. They found that interactive maps can play an important role in tourists’ planning behaviour, and for online tourism marketing.…”
Section: Type Of Processingmentioning
confidence: 99%
“…A room product with conspicuous notifications of a high discount rate and room recommendation rating appears to be a seductive option. As a result, customers are induced to click on the product and to make an immediate purchase (Young Chung et al 2011; Barreda and Bilgihan 2013). In the case of hidden affordance, the findings indicate that the intended lack of information increases the urge to buy.…”
Section: Discussionmentioning
confidence: 99%
“…When all the rooms on a certain day are sold out, customers can no longer consume that product (Smith et al 2015). Perceived sell-out risk generates a feeling of product scarcity, and the anxiety of missing out on a deal encourages customers to immediately make purchasing decisions (Young Chung et al 2011; Sigala 2013).…”
Section: Research Model Developmentmentioning
confidence: 99%